CABARAN PELAKSANAAN UNDANG-UNDANG ISLAM DI THAILAND: Challenges of Implementing Islamic Law in Thailand - Samah, Mahamatayuding (Journal of Shariah Law Research, 2020)
Islamic Law Application in Pattani, Yala, Narathiwat and Satul B.E. 2489 (1946), is the first act declared by the Thai government as an Islamic Law applicable to the courts in four southern Thai provinces. This Act describes the method of deciding Muslim family cases and inheritance. The study was conducted to look at the extent of Islamic Law in the four southern provinces of Thailand and the issues arising from the implementation of the Islamic Law. What is to be concluded is that the position of Islamic Law in southern Thailand remains above what is enacted, very limited both from geographical boundaries that are restricted to the four southern Thai provinces and also to the scope of implementation that is only explored in the field of family and inheritance.